COMPARATIVE STUDY OF SUPERDISINTEGRANTS USING ANTIEMETIC DRUG AS A MODEL - Sandeep, D S; Charyulu, R Narayana; Nayak, Prashant (Journal of Health and Allied Sciences NU, 2015)
In the present investigation comparison of three different superdisintegrants was carried out by formulating orally disintegrating tablets. Promethazine HCl was used as model drug which is an antiemetic drug. Sodium starch glycolate, croscarmellose and crospovidone were selected as superdisintegrants and each one was used in three different concentrations (2%, 3.5% and 5%). The drug-polymer compatibility was ruled out by FTIR studies. A total of nine formulations (PF1-PF9) were made by direct compression. All prepared formulations were evaluated for weight variation, hardness, friability, drug content, disintegration time, wetting time and in vitro drug release parameters. The results of the evaluation parameters for all the nine formulations of promethazine HCl were within the standard limits. The in vitro drug release for promethazine HCl tablets of all the formulations (PF1-PF9) was carried out using phosphate buffer pH 6.8 as dissolution medium. Among all the formulations the tablets formulated with crospovidone (PF7-PF9) have shown 91.43 - 98.43% (maximum) drug release at the end of 10 min than sodium starch glycolate and croscarmellose, hence from the present work, it concluded that among three superdisintegrants crospovidone is the ideal superdisintegrant for formulating oral disintegrating tablets for promethazine HCl.
Keywords: Superdisintegrants; promethazine HCl; sodium starch glycolate; croscarmellose; crospovidone